Recent Advances and Challenges Toward Application of Fibers and Textiles in Integrated Photovoltaic Energy Storage Devices - Rafique, Amjid; Ferreira, Isabel; Abbas, Ghulam; Baptista, Ana Catarina (Nano-Micro Letters, 2023)
Flexible microelectronic devices have seen an increasing trend toward development of miniaturized, portable, and integrated devices as wearable electronics which have the requirement for being light weight, small in dimension, and suppleness. Traditional three-dimensional (3D) and two-dimensional (2D) electronics gadgets fail to effectively comply with these necessities owing to their stiffness and large weights. Investigations have come up with a new family of one-dimensional (1D) flexible and fiber-based electronic devices (FBEDs) comprising power storage, energy-scavenging, implantable sensing, and flexible displays gadgets. However, development and manufacturing are still a challenge owing to their small radius, flexibility, low weight, weave ability and integration in textile electronics. This paper will provide a detailed review on the importance of substrates in electronic devices, intrinsic property requirements, fabrication classification and applications in energy harvesting, energy storage and other flexible electronic devices. Fiber- and textile-based electronic devices for bulk/scalable fabrications, encapsulation, and testing are reviewed and presented future research ideas to enhance the commercialization of these fiber-based electronics devices. Highlights: 1 Compelling aspects of fiber- and textile-based flexible electrodes are reviewed in detail from the point of view of fabrication, properties, and devices performance. 2 The advances of fibers and textile-based electrodes employed in flexible solar cells and flexible energy storage devices are discussed. 3 The outlook and challenges in employing and developing textile-based flexible electrodes are highlighted.